The Connection of Education for Sustainable Development and Language in African Educational Institutions – A Systematic Literature Review - Ulmer, Nico; Wydra, Kerstin (Journal of Contemporary Issues in Education, 2022)
Education for Sustainable Development (EfSD) gained global momentum in recent years. However, little is understood about the connection of EfSD and language, which was described as being among the most underestimated and under-researched parameters of sustainable development. In order to fill this gap, this paper systematically reviews scientific literature on the connection of EfSD and language. In the resulting 33 papers which exclusively dealt with language and EfSD in an African educational setting, most authors used theoretical (28) as opposed to empirical methods (5). Existing research mostly focused on a general educational context (27), followed by lower education (5) and higher education (1). Almost all authors recommended further research into African languages (32), highlighting the need to integrate African languages and indigenous knowledge systems in order to support various development agendas. Further neglect of the language factor might otherwise endanger the implementation of the Sustainable Development Goals.